Adolescente vítima de abuso sexual e musicoterapia: uma revisão sistemática - Suzuki, Denise Chrysostomo [UNIFESP] (2019)
Objective: To understand the use and meaning of music therapy for adolescent victims of sexual abuse in childhood and/or adolescence attended by health services by qualified music therapist. Method: Qualitative systematic review using the acronym PICo, as Population: adolescents victims of sexual abuse; Interest: music therapy and; Context: public and private health services. It used as main descriptors “music therapy”, “sexual abuse” and “adolescent”. The search used the databases: Capes, Ebsco, Lilacs, Pubmed, Scopus, Web of Science and Music Therapy Perspectives, Journal of Music Therapy, British Journal of Music Therapy. Manual search strategies by footnote chasing, citations and author were used too. We used the manuals: "Joanna Briggs Institute Rewiers' Manual" (JMI Rewier's Manual) and the Handbook for Synthesizing Qualitative Research by Sandelowski and Barroso. Inclusion criteria were: 1) case studies and qualitative studies; 2) ages 10 to 19 years; 3) outpatient care and/or public and private health services 4) Intervention description and time of treatment. “Suspected sexual abuse " was determined as exclusion criteria. Results: The research covered the period from 1992 to 2018. Seven articles were included. The results were summarized and two categories were created: 1) music therapy potentials and 2) music therapy for adolescents. Conclusion: Music therapy facilitates the communication of feelings and disclosure of sexual abuse; helps to cope with anger, guilt and shame; favors the therapeutic bond; It is a less confrontational therapy; It favors self esteem and self confidence.